(untitled) (LIS TODAY, 2022)
The free flow of information is a fundamental principle for bridging the gaps between have and have not. ICT has a major impact of materials for research. Innovationin ICT has brought radical changes in the way information is generated, stored, processed and disseminated. Recent advances in converging technologies especially Internet and web technology has paved the way to create the open access archives on repositories. The objective of the open access movement is to make scholarly articles freely available in digital form to anyone anywhere in the world. The open access and open archives movement, the need for changes in the scholarly communication to remove barriers to access.